Relationships between Running Biomechanics, Hip Muscle Strength, and Running-Related Injury in Female Collegiate Cross-country Runners - Elena N. Venable; Lily A. Seynaeve; Scott T. Beale; Albert Gamez Jr.; Antoinette Domingo; Michael D. Rosenthal; Mitchell J. Rauh (International Journal of Sports Physical Therapy)
# Background